2015
DOI: 10.2147/ppa.s87551
|View full text |Cite
|
Sign up to set email alerts
|

Interventional tools to improve medication adherence: review of literature

Abstract: Medication adherence and persistence is recognized as a worldwide public health problem, particularly important in the management of chronic diseases. Nonadherence to medical plans affects every level of the population, but particularly older adults due to the high number of coexisting diseases they are affected by and the consequent polypharmacy. Chronic disease management requires a continuous psychological adaptation and behavioral reorganization. In literature, many interventions to improve medication adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
202
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(235 citation statements)
references
References 107 publications
3
202
4
10
Order By: Relevance
“…Most interventions associated with adherence improvements are not associated with improvements in other outcomes; indeed, in the last few decades, the degree of nonadherence has remained unchanged 19. In an older meta-analyis by Roter et al,25 no single strategy or programmatic focus showed any clear advantage compared with any other, and comprehensive interventions combining cognitive, behavioral, and affective components were more effective than single-focus interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Most interventions associated with adherence improvements are not associated with improvements in other outcomes; indeed, in the last few decades, the degree of nonadherence has remained unchanged 19. In an older meta-analyis by Roter et al,25 no single strategy or programmatic focus showed any clear advantage compared with any other, and comprehensive interventions combining cognitive, behavioral, and affective components were more effective than single-focus interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that less than half of the participants used the pill organizer, limited our ability to assess the impact of this simple intervention. Previous studies have shown that reminder packaging has a positive impact on medication adherence 34. We also used a self-reported adherence measure.…”
Section: Discussionmentioning
confidence: 99%
“…Teach-back method is an efficient patient counseling method which not only provides counseling to the patient but also assesses patients' understanding of provided information [11]. It involves initially providing all necessary information regarding drug to the patient, including indication, side effects, precautions, and frequency of the drug, after providing this information, the patient will be asked openended questions such as "when to take this drug," "for what this drug is given," "how to take the drug," "what should you avoid while taking the drug," and "how often you should take the medicine."…”
Section: Introductionmentioning
confidence: 99%